Characterization of immune cells and cytokine localization in the rat utero-placental unit mid- to late gestation. (August 2015) - Tessier, Daniel R.; Raha, Sandeep; Holloway, Alison C.; Yockell-Lelièvre, Julien; Tayade, Chandrakant; Gruslin, Andrée
Highlights: TNFα and IFNγ co-localized with uNK cells to the rat mesometrial triangle. TNFα and IL-10 demonstrated a gestation-specific distribution in the rat mesometrial triangle. IFNγ-positive nucleated fetal blood cells were observed mid-gestation. IL-10 and neutrophils co-localized to the rat mesometrial triangle. The CD68 macrophage marker should not be used for quantification in rat uterine tissue. Abstract: The success of pregnancy is dependent on the precise regulation of the immune response within the utero-placental environment. Rats are beginning to be widely used as a model for human immune-related pregnancy complications. However, our knowledge of immune cells and cytokine localization in the rat utero-placental tissue is limited. The current study aimed to localize the immune cell populations, including uterine natural killer (uNK) cells, neutrophils, and macrophages within the rat utero-placental unit at two crucial gestational ages, gestational days 15.5 and 18.5. In addition, we characterized the distribution of the cytokines TNFα, IFNγ, and IL-10 in the utero-placental regions at both the above-mentioned gestational ages. Our study has demonstrated co-localization TNFα and IFNγ with uNK cells in perivascular regions of the rat mesometrial triangle at both gestational ages. Neutrophils and IL-10-positive cells were localized at the maternal–fetal interface and in the spiral artery lumen of the rat mesometrial triangle at both gestational ages. TNFα and IL-10 demonstrated a temporal change in the localization from GD15.5 to GD18.5, which coincides with the leading edge of trophoblast invasion into the mesometrial triangle. The current study furthers our knowledge of the localization of uterine immune cells and relevant cytokines, and provides a base from which to research the function of these immune cells and cytokines during rat pregnancy as a model to study human immune-related pregnancy complications.